Analysis of the mitochondrial COI gene and its informative potential for evolutionary inferences in the families Coreidae and Pentatomidae (Heteroptera) - Souza, H. V. [UNESP]; Marchesin, S. R. C.; Itoyama, M. M. [UNESP] (Funpec-editora, 2016)
The mitochondrial cytochrome oxidase subunit 1 (COI) gene is one of the most popular markers used for molecular systematics. Fragments of this gene are often used to infer phylogenies, particularly the region near the 5'-end, which is used by the DNA Barcoding Consortium. With a growing number of sequences being deposited in the DNA barcoding database, there is an urgent need to understand the evolution of this gene and its evolutionary relationship among species; it is also important to analyze the informative potential of the gene for phylogenetic inferences for each group used. In this study, the COI gene was divided into three distinct regions: a 5'-region, a central region, and a 3'-region. The nucleotide composition of these regions was analyzed, and their potential for making informative phylogenetic inferences using species in the families Coreidae and Pentatomidae (Heteroptera) was assessed. It was found that the same region in the COI gene may present different behaviors for each family analyzed, and that using additional regions from the same gene may even prejudice the analysis.
Keywords: COI; Mitochondrial DNA; Heteroptera; Phylogeny; Molecular systematics